Migration and Interregional Employment Redistribution in the United States - Greenwood, Michael J.; Hunt, Gary L. (American Economic Review, 2016)
During the 1970's the South and West census regions accounted for 89.9 percent of incremental U.S. population and 72.5 percent of incremental nonagricultural employment. These figures are sharply higher than corresponding figures for any other decade in U.S. history. For example, during the 1930's the South and West gained 65.4 percent of incremental national population, which was the highest share previously recorded. The immediate cause of the interregional population shifts is fairly heavy net out-migration from the Northeast and North Central regions to the South and West, combined with birth rates that are near historical low levels. Interactive relationships that cause employment growth and migration to reinforce one another are probably operating, but these relationships are not well understood. They are the focus of this paper. Using a new and unique set of time-series data on migration and employment, we develop and estimate a time-series model of migration and employment growth for each of 171 U.S. regions. Our primary emphasis in this paper is on the 57 major metropolitan